2014
DOI: 10.1080/15475441.2014.917557
|View full text |Cite
|
Sign up to set email alerts
|

Sentence Repetition in Deaf Children with Specific Language Impairment in British Sign Language

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractChildren with specific language impairment (SLI) perform poorly on sentence repetition tasks across different spoken languages. Up to this point, sentence repetition has not been investigated in children who have SLI in a signed language. Users of a natural sign language encode different sentence meanings through their choice of signs and by altering the sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 34 publications
2
25
0
1
Order By: Relevance
“…As predicted, chronological age influenced performance on the syntactic task for both native and nonnative signers (see Tables and Figures ). This result for ASL is consistent with findings from other signed languages—Sign Language of the Netherlands (Hermans et al., ) and BSL (Marshall et al., )—showing syntactic development with age, and is compatible with research on spoken languages (Sutter & Johnson, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As predicted, chronological age influenced performance on the syntactic task for both native and nonnative signers (see Tables and Figures ). This result for ASL is consistent with findings from other signed languages—Sign Language of the Netherlands (Hermans et al., ) and BSL (Marshall et al., )—showing syntactic development with age, and is compatible with research on spoken languages (Sutter & Johnson, ).…”
Section: Discussionsupporting
confidence: 91%
“…Siegel and Ryan (1988), for example, found that children with learning disabilities performed significantly more poorly than typically developing children on grammatical error correction tasks. The current results add to the growing literature of identifying language difficulties in children using signed language: BSL (Herman, Rowley, Mason, & Morgan, 2014;Marshall et al, 2014;Mason et al, 2010;Morgan, Herman, & Woll, 2007;Woll & Morgan, 2012) and ASL Quinto-Pozos et al, 2013, Quinto-Pozos, Forber-Pratt, & Singleton, 2011. These findings suggest that reliable assessment tools may need to be developed for specific language backgrounds, such that nonnative signers' scores should be compared to nonnative norms and native signers' scores should be compared to native norms (Herman, Holmes, & Woll, 2001;Mann & Marshall, 2012).…”
Section: Additional Learning Disabilities Affect Primarily the Performentioning
confidence: 59%
See 1 more Smart Citation
“…The results of the current study extend previous descriptions of deaf children with sign language impairments in their nonsense sign repetition (Woll and Morgan ), sentence repetition (Marshall et al . under review) and semantic fluency (Marshall et al .…”
Section: Discussionsupporting
confidence: 90%
“…They were shown to be effective in identifying deaf, school‐age children with and without specific language impairment (SLI) when tested in sign modality (Marshall et al . ). The SRep task is complex: it involves auditory perception of the stimuli and reproduction of them.…”
Section: Introductionmentioning
confidence: 97%